A System of Ethnojournalism Assignments for Students of "Folk Art Culture" Curriculum - Viktoriya Y. Prokofeva (Publishing house "Sreda", 2020)
The "Journalism in the Ethnocultural Sphere" discipline belongs in the basic part of "Folk Art Culture" higher educational field of study curriculum, which is in the process of theoretical development and search for methodological approaches to its teaching. The article represents a development of practical assignments in this discipline. Methods. Based on the author's own pedagogical experience in the field of teaching ethno-journalism to students of this curriculum in FSBEI of HE "Saint Petersburg State University of Film and Television", a system of practical exercises aimed at development of general cultural and professional competencies has been developed. The assignments are divided into five topics; the students are expected to work in the field of both ethnocultural studies and journalism. For each practical lesson there are two types of assignments: analytical, which are based on a theoretical understanding of ethnocultural material (discussion questions), as well as work with mass media data, and creative tasks, which include creating journalistic texts of different genres on ethnocultural topics. It can be concluded, that the results of preparatory and classroom work with the proposed tasks suggest a successful completion of the discipline by future specialists in the field of folk art culture, as well as demonstrate their interest in ethnocultural knowledge and ethnojournalistic activity.